Helvella sublactea sp. nov. (Helvellaceae) from southwestern China - Wang, Miao; Zhao, Yong-Chang; Zhao, Qi; Zhou, De-Qun (Phytotaxa, 2016)
A new species, Helvella sublactea, is discribed from southwestern China using morphological and molecular phylogenetic evidence. It is morphologically characterized by the combination of the following characters: saddle-shaped or irregular lobed pileus with milky white, greyish beige to taupe hymenium, margin fused with stipe, white receptacle surface glabrous and white stipe with deep longitudinal ribs. Molecular phylogenetic analyses, based on a combined ITS and 28S sequence data, showed that H. sublactea clustered with H. lactea but is clearly distinct from the latter. A description, figures, phylogenetic placement and comparison with similar taxa are presented.